Etos Priyayi dalam Novel Para Priyayi Karya Umar Kayam (The Ethos of Priyayi in the Novel Para Priyayi by Umar Kayam) - Pressanti, Desi Ari (Balai Bahasa Jawa Tengah, 2017)
The gentry is a special group in Javanese society who have their own ways of life in order to maintenance their status. This article described the ethos shown by the gentry in Para Priyayi, a novel by Umar Kayam. This is a qualitative research and the result described descriptively. The data collected by recording events or dialogues in this novel. The data were analyzed using sociology of literature. The result shows that the gentries have some ethos that distinguish them from ordinary people. Key word: gentry, ethos